Primary open-angle glaucoma genes - Fingert, J H (Eye (London), 2011)
A substantial fraction of glaucoma has a genetic basis. About 5% of primary open angle glaucoma (POAG) is currently attributed to single-gene or Mendelian forms of glaucoma (ie glaucoma caused by mutations in myocilin or optineurin ). Mutations in these genes have a high likelihood of leading to glaucoma and are rarely seen in normal subjects. Other cases of POAG have a more complex genetic basis and are caused by the combined effects of many genetic and environmental risk factors, each of which do not act alone to cause glaucoma. These factors are more frequently detected in patients with POAG, but are also commonly observed in normal subjects. Additional genes that may be important in glaucoma pathogenesis have been investigated using quantitative traits approaches. Such studies have begun to identify genes that control the magnitude of important quantitative features of glaucoma that may also be important risk factors for POAG, such as central corneal thickness. Each of these different approaches to study glaucoma genetics is providing new insights into the pathogenesis of POAG.